The Effect of Think Pair and Share Learning Model Ability to Write Short Stories Using Comic Media by Eight Grade Students of SMP Negeri 4 Muara - Siregar, Ezsra; Elinawati Situmorang (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of the think pair and share learning model in improving students' ability to write short stories. The population in this study were eighth grade students of SMP Negeri 4 Muara with a total of population 119 students. The sample of this research is 32 students using random sampling technique. The instrument used to collect data was a short story writing assignment. The method used in this research is an experimental method with a one-group pre-test and post-test design. Learning to write short stories for eighth grade students after using the think pair and share learning model showed relatively good results with an average value of 78.90. Then learning to write short stories before learning with the think pair and share model showed sufficient results with an average value of 67.34. From the t-test analysis it was found that there were significant differences between students after being treated with the think pair and share model and before being treated. Therefore from the results of these data the results of hypothesis testing with the t test are t0 (5.13)> t table (2.04), it has been proven that the null hypothesis (Ho) is rejected and the alternative hypothesis (HÂª) is accepted.